The teacher and the challenges within the teaching and learning field in the XXI Century:: Uma abordagem orientada para o desenvolvimento (Scientific Journal of Eduardo Mondlane University, Serie: Educational Sciences, 2012)
This article argues that in each stage of societal evolution, the learning and teaching process is strongly challenged by technological and environmental changes in both urban and rural areas schools. Findings demonstrate that from the first decades of this Century, six challenges have been felt, namely i) globalization; ii) fight against poverty and creation of national wealth versus social well-being; iii) peace and social stability; iv) democracy; v) creation of ecological conscientiousness and vi) the school itself. These challenges urge the education system to move from its monologic school model to a performative, one which means that the previous monologic or banking teaching and learning model needs to be performative and, not only must it be oriented to the society development, but more open to local community development as well. Furthermore, we dare put forth that if a country wishes a determining education associated with its national development agenda, the performative education seems to be the right option within its three levels, particularly at the university level. To conclude the article looks at the learning and teaching process challenges related to primary, secondary (including technical and vocational) school teachers and university lecturers. This approach also includes challenges on rural development. Although the teacher is the key actor within this process, it can be said that he or she may only succeed by knowing to be a teacher proper. This teacher's role and achievement must be associated with a close articulation of action and cooperation with other four influential actors such as the State, local communities (the civil society), industrial private sector and the school itself.
Keywords: performative education; school teacher; lecturer; development; community